Analisis Pengaruh Pendidikan terhadap Pendapatan Nasional: Pendekatan Model Pooled OLS - Fathoni, Aldy Ahmad; Hamzah, Muhammad Ammar; Mu'tasim, Faisal; Putra, Faiz Rhoditul Khanza (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2025)
This study aims to analyze the effect of education on national income using the Pooled Ordinary Least Squares (POLS) model approach. The data used includes average years of schooling, national income per capita, as well as control variables such as investment in infrastructure, unemployment rate, and inflation. The results of the analysis show that education level has a positive and significant influence on national income per capita, with each one-year increase in average years of schooling increasing income by IDR150 thousand. On the other hand, investment in infrastructure shows a positive but statistically insignificant impact. Unemployment and inflation rates have a negative impact on national income, albeit insignificant. These findings underscore the importance of investing in education as a strategy to improve economic welfare. Policy recommendations include improving access and quality of education as well as developing strategies to reduce unemployment and inflation. This research provides valuable insights for policymakers in formulating sustainable and inclusive economic development measures.